A Study of Immunity for Psychogenic Disease in Oral Region (3rd report) - Hara, Kazuhiko; Ohsawa, Kenzi; Ohsawa, Ichirou; Koike, Kazuyoshi; Kudoh, Itsurou; Gotoh, Minoru; Matuura, Nobuhito (Japanese Journal of Psychosomatic Dentistry, 1995)
A review has been made of the immunological system, especially the relationship between T-cells and the results of mental tests. The results are as follows: The subjects were 42 patients with complaints regarded as psychogenic, namely, 24 cases of tongue pain, 5 cases of psychogenic temporomandibular joints syndrome, 4 cases of psychogenic dry mouth, 3 cases each of tooth and gum pain, and 3 cases of relapsed aphthous stomatitis. Their ages varied from 16 to 76 with an average of 52.3. Method: The patients were classified into those with a of helper-T cell/suppressor-T cell ratio (hereinafter called CD 4/8 ratio) of over 2.0 (hereinafter called the high CD 4/8 ratio group) and those with a ratio of less than 2.0 (hereinafter called the low CD 4/8 ratio group). The review was made of the relationship to the results of mental tests. Results: 89.4% of patients in the low CD 4/8 ratio group were in the III, IV area of CMI, compared with 56.5% in the high CD 4/8 ratio group. The low CD 4/8 ratio group showed a depressive tendency with a slight SDS of Zung and on the Masked Depressionsurvey table of Inoue. Regarding item of B of Kyusyuu Medical Index, the low CD 4/8 ratio group recorded high value of 24.0, and the high CD 4/8 ratio group 16.7.